Current and future tools for determination and monitoring of isocitrate dehydrogenase status in gliomas. Issue 6 (December 2018) - Picca, Alberto; Di Stefano, Anna L.; Sanson, Marc
Abstract : Purpose of review: Hotspot mutations of isocitrate dehydrogenase 1 (R132) or 2 (R172) genes affect 40% of diffuse gliomas, mostly grades II and III. The mutant enzyme produces high quantities of d-2-hydroxyglutarate (D2HG), which reshapes the epigenetic of the cell leading to gliomagenesis. For the clinician, the isocitrate dehydrogenase (IDH) mutation is a major biomarker with diagnostic, prognostic, and predictive consequences. With the development of specific inhibitors and vaccination, it appears also a potential actionable target. Recent findings: IDH status is routinely determined on tumor sample by sequencing and immunohistochemistry detecting the most common mutant protein (IDH1R132H). Recently noninvasive diagnostic approaches have been developed based on the detection of the mutant DNA or the D2HG in body fluids, and the detection of D2HG by magnetic resonance spectroscopy of the brain. Summary: These new techniques open avenues for non invasive diagnostic of glioma in patients not amenable to biopsy, in the preoperative setting and also duringpatients follow-up for evaluation of treatment response and prediction of recurrence.